Medical Tourism in Penang: An Analysis of Stakeholder Identity - R. Chandrashekar,; Ang Jia Ying, (Research in Management of Technology and Business, 2021)
Due to rapid changes in the health-care sector worldwide, hospitals and patients are becoming more globalized. These changes have given rise to a new phenomenon called medical tourism and it has increased significantly in recent years. However, it is not enough if only the national governments steer the medical tourism development but should involve various stakeholders for the growth of the industry. Therefore, the purpose of this study is to identify the main stakeholder and key factor contributing to the development of medical tourism in Penang. The study was focusing on tourism related department and agencies in Penang. The study employed quantitative method and data will be collected by distributing questionnaires to respondents. The data will be analysed by using Statistical Package for Social Science (SPSS) and Microsoft Excel. The results of this study are expected to provide valuable insights to stakeholders and policymakers in devising potential strategies to promote medical tourism in Malaysia.